PROFIT ANALYSIS OF BANANA FRUIT TRADERS IN MEDAN MMTC VILLAGE MEDAN ESTATE - Lubis, Sariyah; Girsang, Echlesia; Pardede , Brian Valdano; Padang, Mean Yulius; Fadilah, Putri Maulidina; Siregar, Tiur Malasari (JURNAL KREASI RAKYAT, 2023)
This study aims to analyze the profits of banana fruit traders who sell in the MMTC traditional market, Medan Tembung sub-district, Medan city. Time of research implementation in May 2023. The data used in this research are primary data and secondary data. Primary data obtained from 5 respondents (banana traders) who were interviewed for this study. Here the analysis is used is the profit analysis of banana traders. The results of the study show that the total acceptance of banana fruit traders in MMTC traditional markets Medan city. Banana sellers spend an initial capital of IDR 25,000,000 for one banana truck and get an average profit of IDR 10,000,000.